Uterine Didelphys, an Uncommon Mullerian Duct Anomaly in a Multiparous Woman with Endometrial Carcinoma (2022)
Uterine didelphys is a rare deformity with most cases associated with favourable pregnancy outcomes. Uterine carcinoma in such uterine malformation is equally rare with many cases diagnosed late due to failed pre-surgery evaluation associated with routine endometrial biopsy. We report a case of incidental uterine didelphys found during surgery in a 62-year-old para 2 +3, woman with endometriod variant of endometrial carcinoma of the right uterus (grade II, and at least stage III). She, successful, had surgery and currently undergoing adjuvant chemoradiation with no complaint. This case demonstrates the possibility of uterine didelphys in a patient with endometrial cancer even when there has been successful pregnancies and deliveries. Clinicians should be aware of this rare possibility especially in a background of preceding repeated miscarriages. Diligently performed endometrial biopsy can still yield adequate specimen for pre-surgery histological diagnosis despite the documented high failure rate associated with the procedure. Where available, contrast-enhanced magnetic resonance imaging is a useful pre-surgery evaluation test with option of exploratory laparotomy performed to avoid delay in diagnosis and treatment of cancers where this is not available but with high index of suspicion.